Pengaruh Optimalisasi Anggaran Pariwisata Terhadap Kunjungan Wisatawan dan Kontribusi Pendapatan Asli Daerah di Kota Jayapura Tahun 2022–2024 - Kevin Ruicosta Pulanda; Maria Kbarek (Universitas Cenderawasih, 2025)
This study aims to analyze the influence of tourism budget optimization on the number of tourist visits and the revenue of Local Original Revenue (PAD) in Jayapura City for the period 2022–2024. The research method employs a quantitative approach using the Path Analysis model. Prior to the analysis, instrument testing and classical assumption testing were conducted. Hypothesis testing was carried out through partial tests, simultaneous tests, and the Sobel test to examine the mediating role. Primary data were collected through questionnaires distributed to 35 respondents from the Tourism Office, Bappeda, the Office of SMEs and Cooperatives, the Transportation Office, and travel agents. The results showed that tourism budget optimization has a positive and significant effect on both tourist visits and the contribution of tourism to PAD, with tourist visits acting as a significant mediating variable. Simultaneously, tourism budget optimization also significantly affects both indicators. Thus, the more optimal the management of the tourism budget, the higher the number of tourist visits and the greater the contribution of the tourism sector to PAD in Jayapura City. Practically, it is recommended that the local government formulate more effective, efficient, transparent, and sustainable tourism budget policies, as well as direct programs toward increasing tourist visits to maximize local revenue. Keywords: Budget Optimization, Tourist Visits, Contribution to Local Original Revenue, Path Analysis